Perfil De Enojo En Estudiantes De Tres Universidades CUMex. Un Estudio Comparativo - Andrade, Norma AngÃ©lica Ortega; Guerrero, Ana MarÃa Rivera; Valadez, MarÃa de los Dolores; Rios, Claudia Adriana Calvillo (European Scientific Journal, ESJ, 2017)
The present study aimed to obtain a profile of the anger in students of the degree in psychology of three universities participating in the Consortium of Mexican Universities (CUMex), through a descriptive-comparative study. 300 students participated in the bachelor's degree in psychology. The research design was non-experimental cross-sectional. Descriptive statistical analyzes of the total sample were carried out, as well as the analysis of variance of a single classification to know if there were significant differences in the anger among the students of the three universities. The results show that in general, the participating population of the three universities is within an average range in this emotion. Regarding the results of the descriptive statistical analysis of the total sample and an analysis of variance of a single classification, statistically significant differences were observed when comparing the three universities, and these differences were found between Guadalajara and Zacatecas; although on average, the students of the three universities score within a normal range of anger. It is possible that these results are natural in students of psychology, which favors the profile of training and its future professional practice